2019
DOI: 10.1021/acssuschemeng.9b01603
|View full text |Cite
|
Sign up to set email alerts
|

To Integrate or Not to Integrate—Techno-Economic and Life Cycle Assessment of CO2 Capture and Conversion to Methyl Formate Using Methanol

Abstract: Utilizing CO 2 to produce value-added chemicals can save environmental and economic impacts. However, these savings are reduced by the cost of CO 2 supply when CO 2 has to be captured from dilute sources. To reduce the cost of CO 2 supply, the combination of CO 2 capture and utilization has been suggested in a single integrated CO 2 capture and utilization (ICCU) process. Although integration is intuitively appealing, a rigorous assessment of the savings by integration is missing. In this work, we evaluate if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…Still, LCA for process selection has been applied for important problems such as the selection of feedstocks (74), catalysts (75), products (76,77), and process routes (78,79). Major interest in comparing process alternatives arises from the assessment of novel process designs to conventional processes, e.g., recently in the area of bio-based production of chemicals (80) or carbon capture and utilization (27).…”
Section: Process Selectionmentioning
confidence: 99%
“…Still, LCA for process selection has been applied for important problems such as the selection of feedstocks (74), catalysts (75), products (76,77), and process routes (78,79). Major interest in comparing process alternatives arises from the assessment of novel process designs to conventional processes, e.g., recently in the area of bio-based production of chemicals (80) or carbon capture and utilization (27).…”
Section: Process Selectionmentioning
confidence: 99%
“…A very recent life cycle assessment indicates that the generation of MF from CO 2 would reduce the global warming impact by 16% as compared with the fossil-based production even when using raw materials and energy from fossil sources. 34 Depending on the concentration of CO 2 in the feed, it is advantageous to integrate the carbon capture reference process Rectisol® (CO 2 adsorption in cold methanol) 35 with the carbon utilization step (up to 46% saving of the electricity demand) realizing an Integrated Carbon Capture und Utilization process (ICCU). Mandatory conditions to achieve the integration is on the one side the use of the same solvent in both processes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…methanol, and on the other side to develop an efficient immobilized catalyst system. 34 In the present paper, we address and fulfill these preconditions for the realization of an ICCU process to produce methylformate (MF) from CO 2 and H 2 . We demonstrate that combining catalytic hydrogenation of CO 2 with reactive distillation provides a strategy to effectively balance these seemingly contradicting requirements in a fully integrated two-step process for production of MF from CO 2 , H 2 and MeOH.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews and papers have discussed the costs and techno-economic feasibility of CO 2 utilization routes, a selection (not exhaustive) of which is the following: Centi and Perathoner (2010), Quadrelli et al (2011), Aresta et al (2013), Centi et al (2013), Barbato et al (2014), Centi and Perathoner (2014), Perathoner and Centi (2014), Laumb et al (2013), Ampelli et al (2015), Dimitriou et al (2015), Pérez-Fortes et al (2016), Naims (2016), Navarrete et al (2017), Ordomsky et al (2017), Senftle and Carter, (2017), Zheng et al (2017), Iaquaniello et al (2018), Koytsoumpa et al (2018), González-Garay et al (2019a), Hepburn et al (2019), Jens et al (2019), , Grim et al (2020), Meunier et al (2020), Mustafa et al (2020), , and Zimmermann et al (2020). Although the conclusions are often contradictory, it is commonly suggested that there still exist large barriers for the implementation and deployment of CCU.…”
Section: Introductionmentioning
confidence: 99%